2013
DOI: 10.1099/jmm.0.051458-0
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous abscess formation in the upper extremity caused by toxigenic Corynebacterium ulcerans

Abstract: Corynebacterium ulcerans is attracting attention as an emerging zoonosis that causes lymphadenitis, dermatitis and respiratory infections. We report here what appears to be the first case of subcutaneous abscess formation in the upper extremity due to toxigenic C. ulcerans in Japan. Awareness of the fact that C. ulcerans can cause a subcutaneous, elastic-hard, lessmobile mass with heat, redness and pain in the extremities is important for differential diagnosis. IntroductionCorynebacterium ulcerans is known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The Ministry of Health, Labour and Welfare reported that effective vaccination enables infants to possess high levels of antibodies against diphtheria leading to a marked decrease in antibody prevalence rates in adults aged >45 years [27]. Effectiveness of vaccination for diphtheria has not been fully evaluated [16, 28, 29], and thus further epidemiological surveys of toxigenic C. ulcerans must be conducted to solve this controversial issue. Veterinarians should consider infection with C. ulcerans in cats with purulent disease, particularly upper respiratory tract diseases such as nasal catarrh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ministry of Health, Labour and Welfare reported that effective vaccination enables infants to possess high levels of antibodies against diphtheria leading to a marked decrease in antibody prevalence rates in adults aged >45 years [27]. Effectiveness of vaccination for diphtheria has not been fully evaluated [16, 28, 29], and thus further epidemiological surveys of toxigenic C. ulcerans must be conducted to solve this controversial issue. Veterinarians should consider infection with C. ulcerans in cats with purulent disease, particularly upper respiratory tract diseases such as nasal catarrh.…”
Section: Discussionmentioning
confidence: 99%
“…In recent epidemiological surveys, toxigenic C. ulcerans was isolated from companion animals such as dogs and cats, and livestock such as cows and sheep; thus, these animals were strongly implicated as sources of human infections [7,9,10]. Twelve cases of diphtheria or diphtheria-like disease associated with toxigenic C. ulcerans have been reported in Japan since toxigenic C. ulcerans was first detected in 2001 [11][12][13][14][15][16][17]. In several cases, patients were confirmed as having had direct contact with dogs or cats with/without dermatitis or respiratory symptoms such as rhinitis [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…This condition requires urgent treatment with diphtheria antitoxin and antibiotics. On the other hand, lymphadenitis by C. ulcerans is curable by antibiotics and drainage (Urakawa et al, 2013). C. ulcerans is a zoonotic agent that infects humans drinking unpasteurized milk or in close contact with infected dogs, cats or various other animal species (Vandentorren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…clinical signs is increasing in industrialized and developing countries (Dewinter et al 2005;De Zoysa et al 2005;Mattos-Guaraldi et al 2008a;Wagner et al 2010;Kamada et al 2012;Urakawa et al 2013). Human infections by C. ulcerans may be fatal and mostly occur in adults with close animal contact (Wellinghausen et al 2002;Lartigue et al 2005).…”
Section: Introductionmentioning
confidence: 99%